Lyrics against images: music and audio description - Igareda, Paula (MonTi Monografías de Traducción e Interpretación, 2014)
Music has been an integral part of films from as far back as the silent movie era, where a piano accompaniment was used to build the narrative and an orchestra was used to drown out the sound of the projector. Music in films can encompass a wide array of elements, from a song to a whistle, and can play many roles, as has been commented upon by many researchers. Due to the relevance of music in film narrative, it is an element which merits attention when it comes to making a film accessible, be it through Audio description, Audio subtitling, Sign Language or Subtitling for the Deaf and Hard-of-Hearing. This article focuses on Audio description (AD) and how music is handled in audio described films. First of all, a brief review of existing AD guidelines will be presented in order to highlight the secondary role given to music insofar as these guidelines focus more on topics such as characters, locations, actions, credits, among others. This will be followed by an analysis of a corpus of audio described films, focusing on the treatment of songs with significant lyrics. Two different scenarios will be considered: on the one hand, films with song lyrics that can be understood by the audience because they share the same language and, on the other, English language films with song lyrics in a foreign language. Finally, this article proposes new approaches to the treatment of music in AD.